Design of a high efficiency and low power rectifier circuitry for piezoelectric generator - Xiao, Wen (2018)
This report presented a two-stage high-efficiency low power active rectifier for the piezoelectric energy harvesting system. In this study, conventional half/full wave rectifiers and two active rectifiers were analyzed and presented. Multiple kinds of comparators and current sources were compared and analyzed. Mathematical equations and results were derived for the power conversion efficiency for the selective parts. Speed and open-loop gain of the comparator were analysed as well as the temperature coefficient for the current source. All the structures were built in advanced Integrated Circuit (IC) technology (Global Foundries 0.18um). The simulation showed that the circuit can reach the highest power conversion efficiency at 87.06% respectively at the frequency of 500Hz with AC voltage amplitude of 1.5V.